1999
DOI: 10.1023/a:1018771906780
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A pilot study was carried out investigating women's sexual health in the postnatal period. Postal questionnaires were sent to a cohort of 158 primiparous women approximately 7 months after delivery. Women who had resumed sexual intercourse were asked a detailed set of questions about problems experienced, sexual practices, frequency of intercourse, satisfaction with sex life, and consultation for postnatal sexual problems. All women were asked about the information they received on postnatal health prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It should be emphasized that the influence of the emotional relationship and mutual relations of the partners or fatigue of the pregnant woman on her sexuality as well as effect on delivery and sexuality after pregnancy are constantly being discussed [33,34]. The role of doctors in this case is huge, because according to studies conducted by Barret et al, only 19% of women talked about sexual problems after giving birth [35].…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the influence of the emotional relationship and mutual relations of the partners or fatigue of the pregnant woman on her sexuality as well as effect on delivery and sexuality after pregnancy are constantly being discussed [33,34]. The role of doctors in this case is huge, because according to studies conducted by Barret et al, only 19% of women talked about sexual problems after giving birth [35].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense the authors report that, six weeks after delivery, most women declare their ability to reach an orgasm was improved in comparison to the period prior to pregnancy. Moreover, Barrett et al (1999) concluded that the difficulty in reaching an orgasm is most marked in the three months following the birth of the baby, returning gradually to pre-pregnant levels. In this sense, Signorello, Harlow, Chekos, and Repke (2000) state that six months after delivery 73.8% of the women included in their study were as likely, or even more likely, to reach orgasms as in the period prior to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…What is also known scientifically about the decline following the initial excitement of marriage is that the decline deepens statistically with age and the duration of the marriage, and is also statistically correlated with the number of children. A series of secondary observations also come up in the literature about a peaking of the phenomenon of reduced sexuality following birth of a child (Barrett et al, 1999). Thus, in one sample of 98 postnatal women, 44% reported a definite loss of sexual desire.…”
Section: Previous Literature On Limited Marital Sexualitymentioning
confidence: 95%
“…However, these data are in their own right significantly substantiating of the clinical observations. (The reader is referred to Barrett et al, 1999;Call, Sprecher, & Schwartz, 1995;Doddridge, Schumm, & Berger, 1987;Frank, Anderson, & Rubinstein, 1978;Greenblatt, 1983;Jasso, 1985;Rao & Demaris, 1995. ) All the statistical data we have seen are in agreement that following an initially high sexual frequency at the beginning of marriage, there is a progressive and surprisingly early and intense decline in the frequency of intercourse.…”
Section: Previous Literature On Limited Marital Sexualitymentioning
confidence: 99%